(3GdebJVH ef GdejRGf ddPgHis - (3eLghds; (3GdPgHj,J (B748 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUdGI hGdSdGe Ydi QShd Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B165 - (3U(B315s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B259 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs